Antibacterial chitosan dressing as well as preparation method and application thereof

By mixing chitosan with copper sulfide nanoparticles and borax solution and freeze-thawing, antibacterial chitosan dressing with excellent antibacterial and mechanical properties was prepared, and the existing antibacterial chitosan dressings were solved. The poor antibacterial properties and easy breakage of existing antibacterial chitosan dressings were solved. Problem, suitable for trauma dressings and reduces production costs.

CN119158071AInactive Publication Date: 2024-12-20YANCHENG TEACHERS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411370708.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The gel composite materials of existing antibacterial chitosan dressings have poor antibacterial properties, are prone to breaking and are not easy to shape, which limits their application and large-scale production in the medical field.

Method used

The chitosan-acetic acid solution is mixed with polyvinyl alcohol solution, and copper sulfide nanoparticles and borax solution are added. Antibacterial chitosan dressing is prepared after freeze-thawing treatment, and copper sulfide nanoparticles are synthesized by hydrothermal method to improve the antibacterial effect and Mechanical properties.

Benefits of technology

It improves the antibacterial effect and mechanical properties of antibacterial chitosan dressings, making them less likely to break, is suitable for trauma dressings, and the preparation process of copper sulfide nanoparticles is environmentally friendly and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158071A_ABST
    Figure CN119158071A_ABST
Patent Text Reader

Abstract

The invention relates to the field of medical dressings, in particular to an antibacterial chitosan dressing and a preparation method and application thereof. Comprising the following steps: mixing a chitosan-acetic acid solution with a polyvinyl alcohol solution to prepare a solution A; adding copper sulfide nanoparticles into the solution A, and uniformly stirring and mixing to obtain a solution B; adding a borax solution into the solution B to obtain a mixed solution, and then freezing and thawing to obtain the antibacterial chitosan dressing. The preparation method of the copper sulfide nanoparticles comprises the following steps: dissolving copper salt and polyvinylpyrrolidone in water to obtain a reaction product A; adding hydrazine hydrate into the reaction product A for reaction to obtain a reaction product B; adding sodium sulfide into the reaction product B for reaction to obtain a reaction product C; and adding polyethylene glycol into the reaction product C for reaction to obtain the copper sulfide nanoparticles. The antibacterial chitosan dressing prepared by the preparation method provided by the invention has excellent mechanical properties after being repeatedly frozen and thawed, can well realize manual wire drawing, and is not easy to break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical dressings, and in particular to an antibacterial chitosan dressing and a preparation method and application thereof. Background Art

[0002] Nosocomial bacterial infection caused by non-healing wounds seriously threatens the health of patients. Traditional fabrics adsorbed with antibiotics or disinfectants used in clinical practice are not only prone to cause bacterial resistance, but also prone to form effusion in the wound, affecting wound healing. Therefore, the design and development of new wound dressings can not only effectively remove excess exudate around the wound, but also achieve rapid wound healing, which is of great significance for wound healing. Antibacterial dressings are functional materials with bactericidal and antibacterial effects. Different textile technologies are used to add an appropriate amount of antibacterial agent to the fiber membrane matrix with unidirectional moisture conduction function or introduce antibacterial groups to modify the matrix, so that the fiber membrane material has antibacterial properties. The organic combination of natural antibacterial polymer materials and nanoparticles can provide a broader spectrum of antibacterial properties and is not easy to produce drug resistance. Chitosan is the product of the deacetylation of the natural polysaccharide chitin. Its degradability, non-toxicity and antibacterial properties make it widely used in many fields such as medical dressings, artificial tissue materials and antibacterial agents. Nanoparticles, such as silver nanoclusters and copper sulfide nanoparticles, have very strong bactericidal ability against bacteria such as Escherichia coli (E.coil), Candida albicans (C.albicans) and Staphylococcus aureus (S.aureus).

[0003] Patents and literatures reported that for the combination of chitosan and nanoparticles, most of them use gel-loaded antibacterial nanoparticles instead of fiber non-woven fabrics for loading. Because of the polycationic nature and rigid chemical structure, chitosan is difficult to form fibers through textile technology. The gel composite materials prepared by these existing methods have the defects of poor antibacterial properties, easy breakage, and difficulty in shaping. Not only does it increase the production cost of the enterprise, but it also easily accelerates bacterial growth and causes wound infection, limiting its application in the medical field, and is not conducive to large-scale production and sales by enterprises. Therefore, it is necessary to develop and optimize the processing methods and process flows of antibacterial chitosan dressings. Summary of the invention

[0004] In order to solve the defect of poor antibacterial performance of gel composite materials in the prior art, the present invention provides an antibacterial chitosan dressing and a preparation method and application thereof.

[0005] The first aspect of the present invention provides a method for preparing an antibacterial chitosan dressing, comprising: mixing a chitosan-acetic acid solution with a polyvinyl alcohol solution to obtain a solution A; adding copper sulfide nanoparticles to the solution A, stirring and mixing to obtain a solution B; adding a borax solution to the solution B to obtain a mixed solution, and then freezing and thawing to obtain an antibacterial chitosan dressing;

[0006] The preparation method of the copper sulfide nanoparticles comprises: dissolving a copper salt and polyvinyl pyrrolidone in water to obtain a reaction product A; adding hydrazine hydrate to the reaction product A, stirring for 3 minutes to 7 minutes, and obtaining a reaction product B; adding sodium sulfide to the reaction product B, reacting at 50° C. to 65° C. for 1.5 hours to 2.5 hours, and obtaining a reaction product C; adding polyethylene glycol to the reaction product C, reacting at room temperature for 20 hours to 28 hours, and obtaining the copper sulfide nanoparticles;

[0007] The mass ratio of the copper salt to the polyvinyl pyrrolidone is 15-19:235-245; the mass volume ratio of the copper salt to the hydrazine hydrate is 15-19 mg:25-30 μL; the mass ratio of the polyvinyl pyrrolidone to the sodium sulfide is 235-245:300-305; the mass ratio of the sodium sulfide to the polyethylene glycol is 300-305:3-5.

[0008] In some embodiments of the present invention, the copper salt is copper chloride, copper nitrate or copper sulfate.

[0009] In some embodiments of the present invention, the mass fraction of chitosan in the chitosan-acetic acid solution is 1% to 2%; the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 8% to 12%; the volume ratio of the chitosan-acetic acid solution to the polyvinyl alcohol solution is 1 to 2:1 to 2;

[0010] The molar concentration of the borax solution is 0.015 to 0.025 M;

[0011] The volume ratio of the solution A to the copper sulfide nanoparticles is 100:3-4; the volume ratio of the solution B to the borax solution is 20-21:1.

[0012] In some embodiments of the present invention, the copper sulfide nanoparticles have a particle size of 140 nm to 150 nm.

[0013] In some embodiments of the present invention, copper sulfide nanoparticles are added to the solution A after removing bubbles; and the borax solution is added to the solution B after removing bubbles.

[0014] In some embodiments of the present invention, the method for removing bubbles in the solution A and the solution B is ultrasound.

[0015] In some embodiments of the present invention, the ultrasonic time is 25 min to 35 min.

[0016] In some embodiments of the present invention, the number of freeze-thaw cycles is 3 to 5 times.

[0017] In some embodiments of the present invention, during freeze-thaw, the freezing temperature is -25°C to -15°C, and the melting temperature is 24 to 28°C.

[0018] The second aspect of the present invention provides an antibacterial chitosan dressing prepared by the preparation method.

[0019] The third invention of the present invention provides the use of the antibacterial chitosan dressing in the preparation of wound dressing.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a method for preparing an antibacterial chitosan dressing. Polyethylene glycol is added as a protective agent during the preparation of copper sulfide nanoparticles to control the particle size and improve stability. The prepared copper sulfide nanoparticles are used to prepare antibacterial chitosan dressings. The copper sulfide nanoparticles can be efficiently loaded on modified chitosan, and can better improve the antibacterial effect of the antibacterial chitosan dressing. At the same time, the preparation method provided by the present invention can prepare an antibacterial chitosan dressing with better mechanical properties.

[0022] In the present invention, in order to increase the fluidity and reduce the viscosity of the polyvinyl alcohol (PVA) / chitosan (CS) mixed gel solution, the concentration of the PVA solution and the concentration of the chitosan-acetic acid solution were respectively reduced in subsequent experiments, and the effect of cross-linking with different concentrations of borax was investigated, and the optimal reaction conditions for preparation were gradually explored using a single factor analysis method. The antibacterial chitosan dressing prepared by the preparation method provided by the present invention has excellent mechanical properties after repeated freezing and thawing, can well realize manual wire drawing, and is not easy to break.

[0023] For the synthesis of copper sulfide nanoparticles (CuS NPs), the present invention uses copper chloride and sodium sulfide as raw materials, and generates the target product by hydrothermal synthesis. The present invention explores the influence of raw material molar ratio, reaction temperature and reaction time on the reaction, and obtains the optimal reaction conditions. The CuS NPs synthesis method provided by the present invention uses water as the reaction medium, and prepares nanoparticles with good crystallization and controllable morphology by heating the reactor, and the preparation process does not produce a large amount of toxic waste, such as organic matter, waste gas, etc., which is environmentally friendly and can effectively reduce the cost of enterprises to treat three wastes. Copper sulfide nanoparticles (CuSNPs) are widely used in the biomedical field due to their excellent photothermal and catalytic properties and low biological toxicity. Under near-infrared light irradiation, narrow bandgap p-type semiconductor CuS NPs show efficient photothermal (PTT) and photodynamic (PDT) conversion efficiency. At the same time, CuS NPs have good biodegradability, can effectively participate in the body's metabolism, and are promptly excreted from the body, effectively avoiding the toxic side effects caused by the residues of nanoparticles in the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the chemical structure formula of chitosan.

[0025] Figure 2 UV spectrum of CuS NPs.

[0026] Figure 3 Infrared spectrum of CuS NPs.

[0027] Figure 4 This is the X-ray diffraction (XRD) analysis diagram of CuS NPs.

[0028] Figure 5 Particle size analysis diagram of CuS NPs.

[0029] Figure 6 This is the Zeta potential analysis diagram.

[0030] Figure 7 is the surface morphology characteristic diagram of CuS NPs; Figure 7 a is a scanning electron microscope (SEM) image; Figure 7 b is a transmission electron microscopy (TEM) image.

[0031] Figure 8 Photothermal performance diagram of CuS NPs at different powers

[0032] Fig. 9 This is a sample picture of the antibacterial hydrogel dressing.

[0033] Fig.10 Photothermal performance diagram of antibacterial hydrogel dressing at different powers

[0034] Fig.11 This is the antibacterial plate diagram of the antibacterial hydrogel dressing. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with specific examples, but it should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0036] 1. Instruments and Reagents

[0037] Table 1 Experimental instruments

[0038]

[0039]

[0040] Table 2 Experimental reagents

[0041]

[0042] Patents and literatures reported that chitosan and nanoparticles are combined by gel-loaded antibacterial nanoparticles, rather than fiber nonwovens. Because of its polycationic nature and rigid chemical structure, chitosan is difficult to form into fibers through textile technology. The defects of gel composite materials, such as poor air permeability, poor moisturizing and antibacterial properties, easy breakage, and difficulty in shaping, not only increase the production costs of enterprises, but also cause wound infections due to the easy acceleration of bacterial growth, which limits its application in the medical field and is not conducive to large-scale production and sales by enterprises.

[0043] The invention provides a method for preparing an antibacterial chitosan dressing, comprising: mixing a chitosan-acetic acid solution with a polyvinyl alcohol solution to obtain a solution A; adding copper sulfide nanoparticles to the solution A, stirring and mixing, to obtain a solution B; adding a borax solution to the solution B to obtain a mixed solution, and then freezing and thawing to obtain an antibacterial chitosan dressing;

[0044] The preparation method of the copper sulfide nanoparticles includes: dissolving 15mg-19mg of copper salt and 235mg-245mg of polyvinyl pyrrolidone in 100mL of water to obtain a reaction product A; adding 25-30μL of hydrazine hydrate to the reaction product A, stirring for 3min-7min, and obtaining a reaction product B; adding sodium sulfide to the reaction product B, reacting at 50°C-65°C for 1.5h-2.5h, and obtaining a reaction product C; adding polyethylene glycol to the reaction product C, and reacting at room temperature for 20h-28h to obtain the copper sulfide nanoparticles. The copper sulfide nanoparticles provided by the present invention can be efficiently loaded on modified chitosan, and can better improve the antibacterial effect of antibacterial chitosan dressings. At the same time, the preparation method provided by the present invention can produce an antibacterial chitosan dressing with better mechanical properties.

[0045] Embodiment 1:

[0046] 1. Synthesis of modified chitosan gel

[0047] Take a certain amount of chitosan (structural formula Figure 1 As shown in the figure, the chitosan solution (shown) was dissolved in 2% glacial acetic acid by mass, and the chitosan solutions of different concentrations were obtained by stirring and dissolving, and chitosan-acetic acid solutions of 1%, 2%, 3%, and 4% by mass were prepared respectively. In the initial experiment, 4% chitosan-acetic acid solution was selected for subsequent experiments. A certain amount of polyvinyl alcohol (PVA) and deionized water were stirred and dissolved to prepare PVA solutions of different concentrations, and PVA solutions of 10%, 15%, and 20% by mass were prepared respectively. In the initial experiment, 20% PVA solution was selected for subsequent experiments.

[0048] Chitosan-acetic acid solution and PVA solution were first pre-tested in a volume ratio of 1:1. The mixed solution was thoroughly stirred and mixed, and a large number of bubbles were removed by ultrasound for half an hour. Borax (0.01-0.04M, 1mL) solution was added to the mixed solution for cross-linking, and after thorough stirring and mixing, it was poured into a watch glass, and ultrasound was continued for half an hour to completely remove residual bubbles. The watch glass was placed in a refrigerator for freeze-thaw, that is, placed at -20°C overnight, taken out and thawed at room temperature, and then placed in -20°C again overnight for freezing after sufficient thawing. The freeze-thaw was repeated 3 to 5 times to obtain a PVA / CS mixed gel as a modified chitosan gel for the preparation of antibacterial dressings. Different PVA / CS mixed gels were prepared by repeating the above synthesis steps using chitosan-acetic acid solution and PVA solution of different concentrations.

[0049] 2. Preparation of copper sulfide nanoparticles (CuS NPs)

[0050] CuS NPs were prepared by hydrothermal method, and the preparation method was as follows: 15 mg to 19 mg of cupric chloride dihydrate and 235 mg to 245 mg of polyvinyl pyrrolidone (PVP K30) were weighed and dissolved in 100 mL of deionized water. Then, 25 to 30 μL of hydrazine hydrate (N2H4·H2O) was added to the above reaction solution, and after stirring for 3 min to 7 min, 300 mg to 305 mg of sodium sulfide nonahydrate (Na2S·9H2O) was quickly added to the solution and stirred at 50°C to 65°C for 1.5 h to 2.5 h. Subsequently, when the solution was cooled to room temperature, 5 mg of polyethylene glycol (PEG) (PEG-2000 or PEG-4000, PEG-2000 was used in this embodiment) was immediately injected into the solution, and the reaction was kept at room temperature for 20 h to 28 h to synthesize CuS NPs. The mixture was centrifuged at 10000 rpm for 10 min and washed with deionized water for 3 to 5 times to obtain the pure product of CuS NPs.

[0051] In the above method, any value within the parameter range can be selected to obtain copper sulfide nanoparticles with similar structure. Specifically, the following method is used in this embodiment to prepare CuS NPs: 17 mg of copper chloride dihydrate and 240 mg of polyvinyl pyrrolidone (PVP K30) are weighed and dissolved in 100 mL of deionized water. Then 29.4 μL of hydrazine hydrate (N2H4·H2O) is added to the above reaction solution, and after stirring for 5 min, 303 mg of sodium sulfide nine hydrate (Na2S·9H2O) is quickly added to the solution and stirred at 60 ° C for 2 h. Subsequently, when the solution is cooled to room temperature, 5 mg of polyethylene glycol (PEG) (PEG-2000 or PEG-4000 can be used, PEG-2000 is used in this embodiment) is immediately injected into the solution, and the reaction is maintained at room temperature for 24 h to synthesize CuSNPs. Centrifuge at 10000 rpm for 10 min, wash with deionized water 3 times, and obtain the pure product of CuS NPs.

[0052] The obtained pure CuS NPs product was freeze-dried at -40℃~-10℃ for 24h, and dark green cotton-like powder was collected. After freeze-drying, TEM, SEM, XRD, hydrated particle size, Zeta potential, UV spectrum, infrared spectrum, etc. were used to characterize its morphology and structure, and the photothermal properties of CuS NPs were determined.

[0053] 3. Preparation method of antibacterial chitosan dressing:

[0054] A certain amount of chitosan was dissolved in 2% (w / v) glacial acetic acid, and stirred to dissolve to obtain a chitosan-acetic acid solution with a mass fraction of 4%. A certain amount of PVA and deionized water were stirred to dissolve to obtain a PVA solution with a mass fraction of 20%.

[0055] Chitosan-acetic acid solution and PVA solution are first stirred and mixed according to a volume ratio of 1 to 2: 1 to 2 (in this embodiment, a specific volume ratio of 1: 1 is used) to form solution A, and then 600 μL of pure CuS NPs product is added (the volume ratio of solution A to pure CuS NPs product is 100: 3 to 4, and in this embodiment, the specific volume ratio is 100: 3), and stirred and mixed. Ultrasound for half an hour to remove a large number of bubbles. 1 mL of 0.02 M borax solution (the volume ratio of the mixed solution to the borax solution is 20 to 21: 1, and in this embodiment, the specific volume ratio is 20: 1) is added to the mixed solution for cross-linking, and after sufficient stirring and mixing, it is poured into a watch glass, and the ultrasonic wave is continued for half an hour to completely remove the residual bubbles. The surface dish was placed in a refrigerator for freeze-thaw, that is, placed at -25℃~-15℃ overnight, taken out and thawed at room temperature (24~28℃), and after fully thawed, it was placed in -25℃~-15℃ again for overnight freezing, and the freeze-thaw was repeated 3~5 times to obtain PVA / CS@CuS NPs hydrogel, that is, the antibacterial chitosan dressing (such as Fig. 9 Specifically, in this embodiment, the mixture was frozen at -20°C overnight.

[0056] Chitosan-acetic acid solution with a mass concentration of 4% and PVA solution with a volume ratio of 1:1 were selected for mixing and stirring, and 0.04M borax was used as a cross-linking agent. PVA / CS mixed gel solution was prepared under vigorous stirring as a modified chitosan gel. After the 20% PVA solution and 4% chitosan-acetic acid solution were mixed, the viscosity of the solution increased, and the magnetic stirring was uneven. After adding borax, the gel solidified in the flask. After repeated freezing and thawing, the solidification phenomenon could not be alleviated, and the prepared PVA / CS mixed gel solution had poor fluidity and could not be used for subsequent spinning and weaving. In order to increase the fluidity and reduce the viscosity of the PVA / CS mixed gel solution, the concentrations of PVA solution and chitosan-acetic acid solution were reduced in subsequent experiments, and the effect of cross-linking with different concentrations of borax was investigated. The single factor analysis method was used to gradually explore the optimal reaction conditions for the preparation.

[0057] The single factor analysis method was used to gradually explore the optimal reaction conditions for the concentration of PVA solution, chitosan-acetic acid solution and borax in the preparation of antibacterial chitosan dressings. The antibacterial test was also carried out on the prepared antibacterial chitosan dressings.

[0058] 4. Experimental results

[0059] (1) Effect of chitosan-acetic acid solution concentration on the reaction

[0060] Chitosan is insoluble in water but soluble in acidic media, so glacial acetic acid is used for dissolution. In the experiment, it was found that when the concentration of chitosan-acetic acid solution exceeded 4%, it was not fully dissolved and could not be subjected to subsequent reactions. As shown in Table 3, when the chitosan-acetic acid solution was 2% or 1%, it could be mixed with the PVA solution and magnetically stirred. The solution was mixed more evenly, and after adding borax, it would not solidify immediately. Based on the above research results, 2% chitosan-acetic acid solution was selected as the reaction raw material.

[0061] Table 3 Chitosan-acetic acid solution concentration

[0062]

[0063] (2) Effect of PVA solution concentration on the reaction

[0064] The preliminary experimental results show that after 20% PVA solution is mixed with 1% to 4% chitosan-acetic acid solution, it shows different degrees of viscosity increase effect, and the magnetic stirring is uneven. After adding borax for cross-linking, the PVA / CS mixed gel solution shows obvious solidification and cannot be used for the spinning process in subsequent experiments. It is considered to reduce the concentration of PVA solution to improve the above phenomenon, increase the fluidity of PVA / CS mixed gel solution, and prevent the occurrence of solidification. As shown in Table 4, when the chitosan-acetic acid solution is 2%, the concentration of PVA solution is adjusted to observe the flow properties of the mixed solution. The results show that reducing the concentration of PVA solution can effectively increase the fluidity of the mixed solution. Based on the above research results, 10% PVA solution was selected as the reaction raw material.

[0065] Table 4 PVA solution concentration

[0066]

[0067] (3) Effect of borax concentration on the reaction

[0068] The results of the preliminary experiment showed that the concentration of PVA solution was 10%, and the chitosan-acetic acid solution was 2%. They were mixed in a ratio of 1:1. Under the action of magnetic stirring, they could be fully mixed and uniform. However, when 0.04M borax was added for cross-linking, gel curing still occurred to varying degrees. Therefore, the use of the cross-linking agent was reduced, and the concentration of borax was reduced while the total volume remained unchanged. Table 5 shows the effect of borax concentration on the cross-linking degree and gel state of the PVA / CS mixed gel solution. The results show that as the borax concentration approaches 0.02M, the PVA / CS mixed gel solution is fully cross-linked and has excellent mechanical properties.

[0069] Table 5 Borax concentration

[0070]

[0071] Based on the above research results, the optimal preparation conditions for modified chitosan gel are PVA solution concentration of 10%, chitosan solution concentration of 2%, and borax solution concentration of 0.02M.

[0072] (4) Modified chitosan gel drawing test

[0073] The optimal preparation conditions of modified chitosan gel were selected: the concentration of PVA solution was 10%, the concentration of chitosan solution was 2%, the concentration of borax solution was 0.02M, the chitosan-acetic acid solution and PVA solution were mixed and stirred in a volume ratio of 1:1, and borax was used as a cross-linking agent. The modified chitosan gel was prepared under vigorous stirring. The gelled precursor solution was poured into a watch glass, ultrasonically vibrated for half an hour, and then placed in a -20℃ refrigerator for 12 hours. After taking it out, it was thawed at room temperature. The above steps were repeated 3 times to obtain a modified chitosan fiber gel with certain mechanical properties. The gel was injected into a 1mL syringe and drawn under the action of a microinjector. The drawing length was tested and its mechanical properties were evaluated. Under the condition that the above experimental conditions remained unchanged, the freezing time was changed to 24 hours, and the above experiment was repeated to compare the drawing performance.

[0074] Table 6 Freezing time

[0075] Serial number Freezing time (h) Can it be drawn? Drawing length (cm) 1 12 √ 12 2 24 √ 13

[0076] From Table 6, it can be seen that the modified chitosan gel prepared under the optimal reaction conditions has excellent mechanical properties after repeated freezing and thawing, and can well realize manual drawing, laying a foundation for subsequent electrospinning and other work. In addition, from the experimental results, it can be seen that extending the freezing and thawing time has no obvious effect on increasing or decreasing the drawing phenomenon. Therefore, freezing for 12 hours and repeated freezing and thawing can be selected.

[0077] (5) Preparation of CuS NPs

[0078] The key to the success of CuS NPs preparation is the size and morphology of the nanoparticles. Using liquid as a dispersion medium makes it easier to obtain products with small size and certain morphological characteristics, among which hydrothermal synthesis is the most environmentally friendly preparation method. The hydrothermal method is to use water as a reaction medium in a closed reaction container, and to heat the reactor to prepare nanoparticles with good crystallization and controllable morphology. The preparation process does not produce a large amount of toxic waste, such as organic matter, waste gas, etc., which is environmentally friendly and can effectively reduce the cost of enterprises to treat three wastes. The hydrothermal synthesis method is used to prepare CuS NPs in the present invention. CuCl2 and Na2S·9H2O are used as the main reactants, polyvinyl pyrrolidone (PVP) is used as a protective agent, N2H4·H2O is added to create an alkaline solution environment, and CuS NPs are obtained under low temperature (below 100°C).

[0079] (6) Effect of Na2S mass on particle size

[0080] The reaction amount of CuCl2 and Na2S·9H2O during the preparation process affects the particle size of the product CuS NPs. By adjusting the different molar ratios of CuCl2 and Na2S, the reaction process was controlled, CuS NPs were prepared, and their particle size was measured using a nanoparticle size analyzer. Table 7 shows the comparison of the particle size of CuS NPs prepared with different molar ratios of CuCl2 and Na2S·9H2O.

[0081] Table 7 Mass of Na2S

[0082]

[0083]

[0084] From Table 7, we can see that for the same mass of CuCl2 as a reactant, the amount of Na2S·9H2O added to the system will affect the particle size of the final product. As the amount of Na2S·9H2O added decreases, the molar ratio of CuCl2 and Na2S continues to increase, and the particle size of CuS NPs also continues to increase. In order to complete the efficient loading of CuS NPs by the subsequent modified chitosan fiber and improve the antibacterial performance, the particle size of the prepared CuS NPs nanoparticles is as small as possible. From the analysis of experimental data, when the molar ratio of CuCl2 and Na2S is 0.07, the particle size is 143.96nm, and other ratios are all over 150nm, so the mass of Na2S·9H2O is selected as 437mg as the reaction raw material.

[0085] (7) Effect of reaction time on particle size

[0086] Under the condition that the mass of CuCl2 and Na2S·9H2O and the reaction temperature remain unchanged, the reaction time is changed, the hydrothermal reaction is carried out, and the particle size of the reaction product is measured. The reaction process involves the control of two reaction times, namely the 60℃ reaction time and the room temperature standing time.

[0087] Table 8 Reaction time

[0088]

[0089] From Table 8, we can see that when the reaction time is less than 2 hours at 60°C, the reaction is incomplete and no effective product can be obtained. When the reaction time is longer than 2 hours, the particle size of the reaction product will increase. In addition, the standing time at room temperature after the reaction is completed has no effect on the particle size. Therefore, we selected 2h of reaction at 60°C as the optimal reaction time to obtain CuS NPs with smaller particle size.

[0090] (8) Effect of magnetic stirring speed on particle size

[0091] Table 9 Magnetic stirring speed

[0092] Serial number Magnetic stirring speed (r / min) T60℃ / h Particle size (nm) 1 100 2 Reaction not completed 2 200 2 142.89 3 300 2 143.96 4 400 2 Reaction not completed

[0093] From Table 9, we can see that when the speed is 100r / min and the reaction is carried out at 60°C for 2 hours, the reaction is incomplete and no effective product can be obtained. When the speed is as high as 400r / min, the reaction is relatively rapid, which is not conducive to the growth of the crystal structure and the reaction product cannot be obtained. In addition, when the magnetic stirring speed is 200-300r / min, the reaction occurs and a crystal structure with a particle size of about 143nm is generated. The reason may be that the greater the stirring speed, the higher the collision rate between particles, and the shell-core structure is easy to generate; on the contrary, the stirring speed is small, the attraction between adjacent particles decreases, the aggregation reaction is destroyed, and it is not easy to form a core-shell structure. Therefore, we choose a magnetic stirring speed of 200-300r / min as the optimal stirring speed.

[0094] (9) UV spectroscopy characterization of CuS NPs

[0095] The prepared CuS NPs were washed repeatedly to obtain pure particle solution, which was then tested by UV spectroscopy. Figure 2 As shown, CuS NPs have a small absorption peak at 310nm, a large and broad absorption peak at 320-600nm, and the central absorption peak is located near 420nm. Compared with existing studies, the absorption peaks at 310nm and 320-600nm are characteristic absorption peaks of CuS NPs, thus confirming that CuS NPs were successfully prepared by optimizing the synthesis process and conditions.

[0096] (10) Infrared spectroscopy characterization

[0097] In order to evaluate the molecular interactions in CuS NPs, Fourier transform infrared spectroscopy was used to analyze CuS NPs. The absorption peaks in the infrared spectrum correspond to specific vibration modes of the molecules, which are determined by the composition and structure of the molecules. Therefore, infrared spectroscopy can be used to analyze the surface chemical structure of CuS NPs. Figure 3 It can be observed that at 3445cm -1 and 1654cm -1 There are two obvious vibration peaks, corresponding to the stretching vibration of -OH and NH, respectively, indicating that PVP was used as a protective agent in the synthesis and successfully connected to the surface of the prepared CuS NPs, effectively preventing further collision and aggregation of the nanoparticles and achieving effective control of the particle size of the nanoparticles.

[0098] (11) X-ray diffraction analysis

[0099] In order to verify the crystal structure of CuS NPs, we used X-ray diffraction (XRD) analysis. X-ray diffraction phase analysis is a technique that uses the diffraction effect of X-rays in crystalline materials to analyze the structure of materials. Each crystalline material has its own specific crystal structure, including parameters such as lattice type and interplanar spacing. When the sample is irradiated with X-rays with sufficient energy, the substances in the sample are excited and produce secondary fluorescent X-rays (marker X-rays). The crystal surface reflection follows Bragg's law. Qualitative analysis of the compound can be performed by measuring the diffraction angle position (peak position), quantitative analysis can be performed by measuring the integral intensity of the spectral line (peak intensity), and the size and shape of the grains can be detected by measuring the relationship between the spectral line intensity and the angle. Figure 4 As shown in the figure, obvious diffraction peaks were observed at 22.76°, 29.32°, 31.9°, 33.34° and 47.94°, corresponding to the hexagonal arrangement of Cu and S atoms in the Miller index of (101), (102), (103), (006) and (110), respectively. Compared with the JCPDS-2004 standard card, the CuS NPs synthesized by us are inconsistent with those reported in the literature. This shows that the CuS NPs synthesized by us are a new type of structure.

[0100] (12) Particle size analysis and Zeta potential analysis

[0101] CuS NPs were prepared under the optimal reaction conditions. The hydration radius of CuS NPs was detected by dynamic light scattering (DLS) measurement, and the surface charge was analyzed by Zeta potential. Figure 5 and Figure 6 The results showed that the half-peak width of the CuSNPs particle size distribution diagram was narrow, indicating that the particle size was uniform and the hydrodynamic size was 164.3 nm.

[0102] PVP was used as a protective agent to connect to the surface of CuS NPs, and the charge distribution on the surface of the nanoparticles was analyzed by Zeta potential. Figure 5-Figure 6 The results showed that the surface charge of CuS NPs was negative with a potential of -21.5 mV.

[0103] (13) Scanning electron microscopy (SEM) and transmission electron microscopy (TEM)

[0104] In order to observe the surface morphology of CuS NPs more directly, we used scanning electron microscopy and projection electron microscopy for detection. First, we prepared samples for the two electron microscopy tests respectively. The sample for scanning electron microscopy was made by dissolving freeze-dried CuS NPs in water, controlling the sample concentration, and dropping the sample on a silicon wafer with a 10μL pipette, and drying it for testing. The sample for scanning electron microscopy was made by dropping a CuS NPs solution of the same concentration onto a special copper mesh, and drying it for testing. The test results are shown in the figure below. Figure 7 As shown in a and b in the figure, the CuS NPs in the TEM image present a new structural feature, which is a hollow structure with a porous shell, which is mutually confirmed by the XRD test results. The nanoparticles have good monodispersity and uniform size, with an average diameter of about 144-146nm, which is similar to the results of the nanoparticle size analyzer and smaller than the hydration radius detected by DLS. This is because there is a hydration layer on the surface of CuS NPs, and its hydrodynamic size is slightly larger than the TEM test results.

[0105] (14) Photothermal performance

[0106] The photothermal properties of CuS NPs and PVA / CS@CuS NPs antibacterial hydrogel dressings were investigated. Figure 8 As shown in the figure, under 808nm laser irradiation, the temperature of 0.4mg / mL CuS NPs gradually increased within 6 minutes with the increase of laser power, indicating that CuS NPs have good photothermal properties. Similarly, the photothermal properties of the antibacterial hydrogel dressing loaded with CuS NPs were measured at different laser powers. The results are shown in the figure. Fig.10 As shown in the figure, with the increase of laser power, the temperature of PVA / CS@CuS NPs antibacterial hydrogel dressing gradually increased, indicating that the coating of PVA / CS would not affect the photothermal properties of CuS NPs.

[0107] (15) Antibacterial test:

[0108] Gram-positive bacteria (Staphylococcus aureus) were used as model bacteria. The bacterial suspension was mixed with a fixed mass (0.1g-0.5g) of antibacterial chitosan dressing and placed under 808nm (1.5W) laser irradiation for 5min, and the temperature was controlled not to exceed 50℃. Transfer to a shaker at 150rpm and culture at 37℃ for 2h. Take 50μL of the cultured bacterial solution for plating, culture at 37℃ for 24h, and count and record the number of colonies (CFU / mL).

[0109] Specific examples are as follows:

[0110] 10 5 The bacterial suspension with a CFU / mL content was mixed with 0.03 g of blank dressing (without CuS NPs) and 0.03 g of antibacterial chitosan dressing (PVA / CS@CuS NPs antibacterial hydrogel), respectively. After irradiation with 808 nm (1.5 W) laser for 5 min and shaking culture at 150 rpm and 37 °C for 2 h, 50 μL of the cultured bacterial solution (control group), the mixture of the bacterial suspension and blank dressing (blank dressing group), and the mixture of the bacterial suspension and antibacterial chitosan dressing (PVA / CS@CuS NPs antibacterial hydrogel group) were spread on plates and cultured at 37 °C for 24 h. The number of colonies (CFU / mL) formed was counted and recorded.

[0111] Test results such as Fig.11 As shown in the figure, compared with the control group, the PVA / CS@CuS NPs hydrogel treated with laser irradiation had a significant killing effect on bacteria, with a killing rate of more than 95%. The blank dressing (without CuS NPs) group had only limited inhibition and the bactericidal effect was not obvious. The above results show that the antibacterial chitosan dressing (PVA / CS@CuS NPs hydrogel) has excellent antibacterial properties.

[0112] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0113] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an antibacterial chitosan dressing, characterized in that: include: The chitosan-acetic acid solution and the polyvinyl alcohol solution are mixed to prepare solution A; Adding copper sulfide nanoparticles to the solution A, stirring and mixing, to obtain a solution B; Adding borax solution to the solution B to obtain a mixed solution, followed by freeze-thawing to obtain an antibacterial chitosan dressing; The method for preparing the copper sulfide nanoparticles comprises: dissolving a copper salt and polyvinyl pyrrolidone in water to obtain a reaction product A; Add hydrazine hydrate to the reaction product A, and stir for 3 to 7 minutes to obtain a reaction product B; add sodium sulfide to the reaction product B, and react at 50° C. to 65° C. for 1.5 to 2.5 hours to obtain a reaction product C; add polyethylene glycol to the reaction product C, and react at room temperature for 20 to 28 hours to obtain the copper sulfide nanoparticles; The mass ratio of the copper salt to the polyvinyl pyrrolidone is 15-19:235-245; the mass volume ratio of the copper salt to the hydrazine hydrate is 15-19 mg:25-30 μL; the mass ratio of the polyvinyl pyrrolidone to the sodium sulfide is 235-245:300-305; the mass ratio of the sodium sulfide to the polyethylene glycol is 300-305:3-5.

2. The preparation method according to claim 1, characterized in that The copper salt is copper chloride, copper nitrate or copper sulfate.

3. The preparation method according to claim 1, characterized in that: The mass fraction of chitosan in the chitosan-acetic acid solution is 1% to 2%; the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 8% to 12%; the volume ratio of the chitosan-acetic acid solution to the polyvinyl alcohol solution is 1 to 2:1 to 2; The molar concentration of the borax solution is 0.015 to 0.025 M; The volume ratio of the solution A to the copper sulfide nanoparticles is 100:3-4; the volume ratio of the solution B to the borax solution is 20-21:

1.

4. The preparation method according to claim 1, characterized in that: The particle size of the copper sulfide nanoparticles is 140nm-150nm.

5. The preparation method according to claim 1, characterized in that: The copper sulfide nanoparticles are added to the solution A after removing bubbles; and the borax solution is added to the solution B after removing bubbles.

6. The preparation method according to claim 1, characterized in that: The number of freeze-thaw cycles is 3 to 5 times.

7. The preparation method according to claim 1, characterized in that: During freeze-thaw, the freezing temperature is -25℃~-15℃, and the melting temperature is 24~28℃.

8. The antibacterial chitosan dressing prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the antibacterial chitosan dressing according to claim 8 in the preparation of antibacterial dressings.